The Owl and the Nightingale and the English Poems of Jesus College MS 29 (II) - Fein, Susanna, 1950- (Book collections on Project MUSE., 2022)
"Oxford Jesus college MS 29 (II), a thirteenth-century manuscript, contains the longest surviving English verse sequence from period between the Exeter Book and the Harley Lyrics. The sequence is varied in subject, with poems of religious exhortation set beside others of secular pragmatism. Included are: "The Owl and the Nightingale," "Poema Morale," "The Proverbs of Alfred," Thomas of Hales's "Love Rune," "The Eleven Pains of Hell," the prose "Shires and Hundreds of England," the lengthy "Passion of Jesus Christ in English," and twenty-one additional lyrics, most of them uniquely preserved in this manuscript and presented here with accompanying translations in Modern English and scholarly introduction and apparatus"--